SOCS1 Mediates Berberine-Induced Amelioration of Microglial Activated States in N9 Microglia Exposed to β Amyloid - Qi Guo (Hindawi Limited, 2021)
Attenuating β amyloid- (Aβ-) induced microglial activation is considered to be effective in treating Alzheimer’s disease (AD). Berberine (BBR) can reduce microglial activation in Aβ-treated microglial cells; the mechanism, however, is still illusive. Silencing of cytokine signaling factor 1 (SOCS1) is the primary regulator of many cytokines involved in immune reactions, whose upregulation can reverse the activation of microglial cells. Microglia could be activated into two different statuses, classic activated state (M1 state) and alternative activated state (M2 state), and M1 state is harmful, but M2 is beneficial. In the present study, N9 microglial cells were exposed to Aβ to imitate microglial activation in AD. And Western blot and immunocytochemistry were taken to observe inducible nitric oxide synthase (iNOS), Arginase-1 (Arg-1), and SOCS1 expressions, and the enzyme-linked immunosorbent assay (ELISA) was used to measure inflammatory and neurotrophic factor release. Compared with the normal cultured control cells, Aβ exposure markedly increased the level of microglial M1 state markers (P<0.05), including iNOS protein expression, tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and IL-6 releases, and BBR administration upregulated SOSC1 expression and the level of microglial M2 state markers (P<0.05), such as Arg-1 expression, brain-derived neurotrophic factor (BDNF), and glial cell-derived neurotrophic factor (GDNF) releases, downregulating the SOCS1 expression by using siRNA, however, significantly reversed the BBR-induced effects on microglial M1 and M2 state markers and SOCS1 expression (P<0.05). These findings indicated that BBR can inhibit Aβ-induced microglial activation via modulating the microglial M1/M2 activated state, and SOCS1 mediates the process.